Quantitative Phase Imaging Camera With a Weak Diffuser - Lu, Linpeng; Sun, Jiasong; Zhang, Jialin; Fan, Yao; Chen, Qian; Zuo, Chao (Frontiers in Physics, 2019)
We introduce the quantitative phase imaging camera with a weak diffuser (QPICWD) as a practical realization of quantitative phase imaging (QPI) on standard microscope platforms. The QPICWD is a compact stand-alone camera which measures sample induced phase delay under low-coherence quasi-monochromatic illumination by examining the deformation of the speckle intensity pattern. By interpreting the speckle deformation with an ensemble average of the geometric flow, we can obtain the high-resolution distortion field by solving the transport of intensity equation (TIE). Since the phase measured by TIE is the generalized phase of the partially coherent image, instead of the phase of the measured object, we analyze the effect of illumination coherence and imaging numerical aperture (NA) on the accuracy of phase retrieval, revealing that the phase of the object can be reliably retrieved when the coherence parameter (the ratio of illumination NA to objective NA) of the Kohler illumination is between 0.3 and 0.5. We present several applications for the new design including nondestructive optical testing of microlens array with nanometric thickness and imaging of fixed and live HeLa cells. Since the designed QPI camera does not require any modification of the widely available bright-field microscope or additional accessories for its use, it is expected to be adopted by the broader biology and medical community.